RiceVarMap: a comprehensive database of rice genomic variations. Issue Volume 43:Issue D1(2015) (1st October 2014) - Zhao, Hu; Yao, Wen; Ouyang, Yidan; Yang, Wanneng; Wang, Gongwei; Lian, Xingming; Xing, Yongzhong; Chen, Lingling; Xie, Weibo
Abstract : Rice Variation Map (RiceVarMap, http:/ricevarmap.ncpgr.cn ) is a database of rice genomic variations. The database provides comprehensive information of 6 551 358 single nucleotide polymorphisms (SNPs) and 1 214 627 insertions/deletions (INDELs) identified from sequencing data of 1479 rice accessions. The SNP genotypes of all accessions were imputed and evaluated, resulting in an overall missing data rate of 0.42% and an estimated accuracy greater than 99%. The SNP/INDEL genotypes of all accessions are available for online query and download. Users can search SNPs/INDELs by identifiers of the SNPs/INDELs, genomic regions, gene identifiers and keywords of gene annotation. Allele frequencies within various subpopulations and the effects of the variation that may alter the protein sequence of a gene are also listed for each SNP/INDEL. The database also provides geographical details and phenotype images for various rice accessions. In particular, the database provides tools to construct haplotype networks and design PCR-primers by taking into account surrounding known genomic variations. These data and tools are highly useful for exploring genetic variations and evolution studies of rice and other species.